E-Modul Interaktif Berbasis Technopreneurship Pada Pembelajaran Proyek Wirausaha - Siti Aenandari Hadatul Aysi; Leny Noviani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
Efforts to cultivate an entrepreneurial spirit in order to produce a high level of entrepreneurial intention require a separate strategy related to the development of interactive and innovative learning. The development of this strategy must also be adapted to technological developments and the implementation of the applicable curriculum. The purpose of this research is to design interactive e-modules based on technopreneurship in the Curriculum entrepreneurship project learning so that it can be used effectively, so as to increase students' intentions to become entrepreneurs after graduation. Researchers used the literature review research method, by analyzing findings through library data collection, reading and taking notes, and qualitative processing of literature documents. The results of the study state that the design of interactive e-modules based on technopreneurship in merdeka entrepreneurial project learning can be carried out as an effort to increase the effectiveness of learning, namely in creating student entrepreneurial intensity. In addition, technopreneurship-based interactive e-module designs can be integrated into web forms by inserting broad multimedia and content elements at once such as text, images, audio, video, even animations that are appropriate to the technopreneurship topic base in a link